A bismuth-based composite material and its preparation method and application

Preparation of bismuth-based composite materials by solvent thermal method solves the problems of complex process and low efficiency in the existing technology, and realizes the efficient and stable preparation of bismuth-based composite materials, with excellent morphology and catalytic properties, and is suitable for efficient removal of organic pollution by efficiently removing organic pollution. Things.

CN118767950BActive Publication Date: 2025-01-07CHINALCO RES INST OF SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256988.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-01-07
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

In the prior art, the preparation process of bismuth-based composite materials is complex, has low efficiency, is unstable, has uncontrollable product structure and poor morphology, making it difficult to easily and efficiently prepare functional composite materials.

Method used

The mixture of bismuth source, tungsten source, organic solvent and auxiliary agent is heated and solvothermal reaction under closed conditions to prepare a composite material containing bismuth nanosheets and tungsten nanoparticles, which is dissolved by magnetic stirring and in an autoclave. Solvent-thermal reaction was carried out to obtain a stable bismuth-based composite material.

Benefits of technology

It realizes efficient and stable preparation of bismuth-based composite materials, controllable morphology and excellent performance, simplifies the process flow, improves the preparation efficiency, and shows efficient photocatalytic degradation and adsorbing organic pollutants under full spectrum conditions. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118767950B_ABST
    Figure CN118767950B_ABST
Patent Text Reader

Abstract

The present invention discloses a bismuth composite material and its preparation method and application, belonging to the field of material technology. The bismuth composite material is a composite material containing bismuth nanosheets and tungsten nanoparticles, which includes aggregates of bismuth nanosheets and tungsten nanoparticles dispersed and adhered to the surface of the bismuth nanosheets. The preparation method comprises: mixing a bismuth source, a tungsten source, an organic solvent and an auxiliary agent to obtain a mixture; heating the mixture under closed conditions and performing a solvent thermal reaction to obtain a bismuth composite material. The bismuth composite material of the present invention can be used to adsorb or degrade organic pollutants with high efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, and in particular to a bismuth-based composite material and a preparation method and application thereof. Background Art

[0002] With the continuous advancement of science and technology, industry has developed explosively, but it has also brought serious environmental pollution. Photocatalysis as a technology for treating environmental pollution has many advantages, such as: it can degrade wastewater that microorganisms cannot degrade, it only uses light energy, it has low operation and device costs, it does not produce sludge, it does not require additional costs, and it takes up a small area of ​​treatment facilities. Especially in wastewater treatment, it has shown great potential for modern, green, energy-saving and environmental protection, and has gradually become a research hotspot in the field of environmental protection.

[0003] Among the numerous photocatalysts, there are many types of bismuth catalysts, including Bi2O3, Bi2S3, BiOCl, Bi2O2CO3, BiVO4, Bi2MoO6, etc. Among them, BiOCl, as a semiconductor material with unique physical and chemical properties, is widely used in the fields of environment, energy, chemical industry and information technology. The valence band bottom of BiOCl catalyst is low, and it has a strong ability to form hydroxyl radicals (active species) in the photocatalytic process, but its large bandgap (~3.3 eV) brings the problem of difficult excitation of photogenerated electron holes, which shows the disadvantage of low photocatalytic efficiency in application, limiting its practical application effect.

[0004] Therefore, researchers generally combine it with another semiconductor or metal with a corresponding energy band structure to construct a heterojunction / homojunction, and rely on synergistic effects to make up for each other's structural defects to produce a composite catalyst with high efficiency in pollutant degradation. In recent years, nanotechnology has been changing with each passing day, and nano-scale composite bismuth materials have gradually entered people's field of vision. Compared with large-sized macroscopic materials, micro-nano-scale bismuth materials have the advantages of significantly increased specific surface area, quantum confinement effect, and adjustable surface energy, and have received more and more attention.

[0005] At present, the methods for preparing BiOCl are mainly liquid phase methods, including acid thermal method, precipitation method, hydrothermal / solvothermal method, etc. When preparing bismuth-based materials, the acid thermal method and precipitation method often require dissolution in acid, alkali or equivalent, and then heating, filtering, elution and other steps, which are relatively complicated, and can only produce BiOCl at one time. Subsequent steps are still required to obtain composite bismuth materials. The known hydrothermal / solvothermal method can often only obtain a single bismuth material at a time, and two or even three steps are required to finally obtain a bismuth-based composite catalyst with good effect. The preparation efficiency is low and a lot of manpower, financial resources and material resources are wasted. Therefore, from the perspective of preparing functional composite materials, seeking a method that can stably and easily prepare the required composite materials is still a research difficulty in the current academic community. Summary of the invention

[0006] The main purpose of the present invention is to provide a bismuth-based composite material and a preparation method and application thereof, so as to solve the problems of complex process, low efficiency, instability, uncontrollable product structure and poor morphology of bismuth-based composite materials in the prior art.

[0007] In order to achieve the above-mentioned object, according to one aspect of the present invention, a bismuth-based composite material is provided, which is a composite material of bismuth-containing nanosheets and tungsten-containing nanoparticles, which includes aggregates of bismuth-containing nanosheets, and tungsten-containing nanoparticles are dispersed and adhered to the surface of the bismuth-containing nanosheets.

[0008] Furthermore, the bismuth-containing nanosheets interpenetrate each other to form aggregates.

[0009] Furthermore, the bismuth-containing nanosheets are BiOCl nanosheets; and the tungsten-containing nanoparticles are WO3 nanoparticles.

[0010] Furthermore, BiOCl nanosheets belong to the tetragonal system, and WO3 nanoparticles belong to the triclinic system.

[0011] Furthermore, the BiOCl nanosheets have a diameter of 1.5-20 μm and a thickness of 50-400 nm.

[0012] Furthermore, the BiOCl nanosheets have a diameter of 1.5-3 μm and a thickness of 50-200 nm.

[0013] Furthermore, the BiOCl nanosheets have a diameter of 2~20 µm and a thickness of 200~400 nm.

[0014] Furthermore, the X-ray powder diffraction data of the bismuth-based composite material include:

[0015] PDF#06-0249: 11.98-40 (2θ-I), 25.86-100 (2θ-I), 32.50-75 (2θ-I), 3345-95 ( 2θ-I), 40.89-30 (2θ-I), 46.64-35 (2θ-I), 49.70-25 (2θ-I), 54.09-25 (2θ-I);

[0016] PDF#32-1395: 23.14-85 (2θ-I), 23.64-100 (2θ-I), 24.37-100 (2θ-I), 26.62-13 (2θ-I), 28.93-20 (2θ-I), 33.58-35 (2θ-I), 34.10-35 (2θ-I), 41.87-30 (2θ-I).

[0017] According to a second aspect of the present invention, a method for preparing the above-mentioned bismuth-based composite material is provided, the method comprising the following steps:

[0018] S1: mixing a bismuth source, a tungsten source, an organic solvent and an auxiliary agent to obtain a mixture;

[0019] S2: heating the mixture under closed conditions and performing a solvent thermal reaction to obtain a bismuth-based composite material.

[0020] Furthermore, in step S1, the molar ratio of the bismuth source, the tungsten source, the organic solvent and the auxiliary agent is (0.01-0.8): (0.01-0.3): 13.62: (0.001-0.05).

[0021] Furthermore, in step S2, the conditions of the solvent thermal reaction include: a reaction temperature of 150-300° C. and a reaction time of 3-8 h.

[0022] Further, the bismuth source is selected from one or more of bismuth nitrate, bismuth oxide and bismuth chloride.

[0023] Furthermore, the tungsten source is selected from one or more of tungsten hexachloride, sodium tungstate and ammonium paratungstate.

[0024] Furthermore, the auxiliary agent is selected from one or more of aminotrimethylenephosphonic acid, trimethyl 1-hexadecylammonium bromide and ethylenediaminetetraacetic acid.

[0025] Furthermore, the organic solvent is selected from one or more of methanol, ethanol, ethylene glycol, acetone and n-hexane.

[0026] Furthermore, the concentration of tungsten hexachloride is 0.01-0.3 mol / L.

[0027] Furthermore, the concentration of bismuth chloride is 0.01-0.8 mol / L.

[0028] Furthermore, the concentration of trimethyl 1-hexadecyl ammonium bromide is 0.001-0.05 mol / L.

[0029] Furthermore, in step S1, the bismuth source and the tungsten source are first dissolved in an organic solvent, and dissolved by magnetic stirring in an air atmosphere, and then an auxiliary agent is added to the solution, and dissolved by magnetic stirring in an air atmosphere to obtain a mixture; in step S2, the mixture is placed in a high-pressure reactor for solvent thermal reaction.

[0030] Furthermore, in step S2, the product after the solvent thermal reaction is cooled, washed and dried to obtain a bismuth-based composite material.

[0031] Furthermore, the washing is performed by washing with multiple solutions for multiple times, the multiple solutions include water, anhydrous ethanol or methanol; the washing includes washing with water for 2 to 3 times and washing with anhydrous ethanol for 2 to 3 times.

[0032] Furthermore, drying includes one or more of natural air drying, blower drying and drying oven drying.

[0033] According to a third aspect of the present invention, there is provided use of the above-mentioned bismuth-based composite material or the bismuth-based composite material obtained by the above-mentioned preparation method in removing organic pollutants.

[0034] Furthermore, the bismuth-based composite material can remove organic pollutants by adsorbing organic pollutants in water or photocatalytically degrading organic pollutants in water.

[0035] Furthermore, the photocatalysis adopts full-spectrum catalysis.

[0036] Furthermore, the organic pollutants include one or more of rhodamine B, methylene blue, bisphenol A, trimethoprim, and tetracycline.

[0037] Furthermore, the light source for photocatalysis is selected from at least one or more of natural sunlight, simulated sunlight, xenon lamp, high pressure mercury lamp and LED monochromatic light.

[0038] By applying the technical solution of the present invention, the provided bismuth-based composite material has the advantages of diverse morphologies, small sizes, and convenient applications; the preparation method of the above-mentioned bismuth-based composite material provided by the present invention is efficient, stable, simple, easy, green and environmentally friendly, and the product has high controllability; the above-mentioned bismuth-based composite material provided by the present invention can be used to adsorb or degrade organic pollutants with high efficiency, and can especially be used for photocatalytic degradation under full-spectrum conditions, with low requirements, high performance, and significant effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0040] Figure 1 The SEM image of the product obtained in Example 1 of the present invention is shown;

[0041] Figure 2 The XRD picture of the product obtained in Example 1 of the present invention is shown;

[0042] Figure 3 The SEM image of the product obtained in Example 2 of the present invention is shown;

[0043] Figure 4 The figure shows the effect of the composite product obtained in Example 1 of the present invention on the adsorption of pollutants;

[0044] Figure 5 The photocatalytic degradation effect of the composite product obtained in Example 1 of the present invention on pollutants is shown;

[0045] Figure 6 The figure shows the effect of the composite material obtained in Comparative Example 1 of the present invention on the adsorption of pollutants;

[0046] Figure 7 The diagram shows the effect of the composite material obtained in Comparative Example 2 of the present invention on the photocatalytic degradation of pollutants. DETAILED DESCRIPTION

[0047] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0048] In order to solve the above problems existing in the prior art, the present invention provides a bismuth-based composite material, which is a composite material of bismuth-containing nanosheets and tungsten-containing nanoparticles, including aggregates of bismuth-containing nanosheets, and tungsten-containing nanoparticles are dispersed and adhered to the surface of the bismuth-containing nanosheets.

[0049] The bismuth-based composite material of the present invention has a stable microstructure: the bismuth-containing nanosheets are relatively uniform in size and form an aggregate structure by interlacing and crossing each other, and the shape is similar to a 3D structure in the shape of a flower cluster.

[0050] The bismuth-containing nanosheets of the present invention are specifically BiOCl nanosheets; the tungsten-containing nanoparticles are WO3 nanoparticles; the BiOCl nanosheets belong to the tetragonal system, and the WO3 nanoparticles belong to the triclinic system; the bismuth-based composite material of the present invention has the characteristics of small size, stable structure, diverse morphology, and easy application; the specific BiOCl nanosheet has a sheet diameter of 1.5-20 μm and a thickness of 50-400 nm; further, the BiOCl nanosheet has a sheet diameter of 1.5-3 μm and a thickness of 50-200 nm; or the BiOCl nanosheet has a sheet diameter of 2-20 μm and a thickness of 200-400 nm.

[0051] The bismuth-based composite material of the present invention has corresponding diffraction peaks at the following diffraction positions:

[0052] PDF#06-0249: 11.98-40 (2θ-I), 25.86-100 (2θ-I), 32.50-75 (2θ-I), 3345-95 ( 2θ-I), 40.89-30 (2θ-I), 46.64-35 (2θ-I), 49.70-25 (2θ-I), 54.09-25 (2θ-I);

[0053] PDF#32-1395: 23.14-85 (2θ-I), 23.64-100 (2θ-I), 24.37-100 (2θ-I), 26.62-13 (2θ-I), 28.93-20 (2θ-I), 33.58-35 (2θ-I), 34.10-35 (2θ-I), 41.87-30 (2θ-I).

[0054] The tungsten-containing nanoparticles in the bismuth-based composite material of the present invention are dispersed and adhered to the surface of the bismuth-containing nanosheets to form a type I heterostructure composite photocatalyst. This structure is conducive to the transfer of photogenerated electrons and holes to higher and lower potential levels, forming an electron band with stronger oxidation / reduction ability, which is conducive to the generation of active free radicals such as hydroxyl groups that participate in key reactions in the re-catalytic process, thereby producing a high catalytic degradation efficiency that is different from that of general single catalytic materials. In addition, the interlaced and crossed nanosheets are conducive to the multi-level refraction of light on the surface of the sample, fully improving the utilization rate of light in the catalytic process; the nanoparticles are conducive to increasing the overall specific surface area of ​​the catalyst and increasing the number of sites participating in the reaction in the catalytic process. These structural advantages work synergistically with each other to jointly promote the efficiency of the prepared products in the photocatalytic degradation and adsorption processes.

[0055] In order to obtain the above-mentioned bismuth-based composite with excellent structure, the present invention provides a preparation method with simple operation, green and environmental protection, high efficiency and stability, and controllable product morphology:

[0056] S1: mixing a bismuth source, a tungsten source, an organic solvent and an auxiliary agent to obtain a mixture;

[0057] S2: heating the mixture under closed conditions and performing a solvent thermal reaction to obtain a bismuth-based composite material.

[0058] The solvent thermal method provided by the present invention can prepare bismuth-based composite materials in one step, and the product morphology is controllable and has excellent performance, which solves a major problem currently existing in this field and can simply and stably prepare functional bismuth-based composite materials; at the same time, the raw materials used in the method of the present invention have the characteristics of being diverse in type, wide in source, wide in range, and easily available in the market; the preparation process is efficient, stable, simple, easy to operate, and green and environmentally friendly; the composite products are small in size, diverse in morphology, highly controllable, and easy to use.

[0059] The bismuth source in the method of the present invention is selected from at least one of bismuth nitrate, bismuth oxide and bismuth chloride, preferably bismuth chloride; the tungsten source is selected from at least one of tungsten hexachloride, sodium tungstate and ammonium paratungstate, preferably tungsten hexachloride.

[0060] The present invention fully considers the problem of the ultimate use and full reaction of raw materials in the actual operation process, and achieves the purpose that the metal ions (cations) and acid ions (anions) in the main raw materials of a reactant can respectively generate constituent elements in one or more composite products (such as BiOCl nanosheets and WO3 nanoparticles), achieving multiple goals at one stroke, and has the effect of reducing the length of the reaction process and reducing the carbon footprint.

[0061] In the method of the present invention, the organic solvent is selected from at least one of methanol, ethanol, ethylene glycol, acetone and n-hexane; preferably acetone solution; the above solvents have good solubility for raw materials.

[0062] In the method of the present invention, the auxiliary agent is selected from at least one of aminotrimethylenephosphonic acid (ATMP), trimethyl 1-hexadecylammonium bromide (CTAB) and ethylenediaminetetraacetic acid (EDTA), preferably CTAB; the auxiliary agent can form an intermediate complex with the metal (bismuth and tungsten) and the organic group (solvent) in the solution to achieve the purpose of promoting product formation and controlling product morphology.

[0063] Therefore, in order to achieve the purpose of the above-mentioned multiple components synergistically promoting the formation of products and controlling the morphology of products, the present invention limits the content of each component: the concentration of tungsten hexachloride is 0.01~0.3mol / L, the concentration of bismuth chloride is 0.01~0.8mol / L, and the concentration of trimethyl 1-hexadecyl ammonium bromide is 0.001~0.05mol / L. In particular, the present invention takes into account the occurrence of side reactions, product yield, structural morphology and application effects, and preferably 0.03 mol / L of tungsten hexachloride, 0.08 mol / L of bismuth chloride, and 0.01 mol / L of CTAB. Specifically, the molar ratio of bismuth source, tungsten source, organic solvent and auxiliary agent in the raw material of the present invention is (0.01~0.8): (0.01~0.3): 13.62: (0.001~0.05); more specifically, the molar ratio of bismuth source, tungsten source, organic solvent and auxiliary agent is 0.03: 0.08: 13.62: 0.01.

[0064] In order to stably control the solvent thermal reaction process to obtain a product with stable structure and controllable morphology, the conditions of the solvent thermal reaction in step S2 of the present invention include: a reaction temperature of 150-300°C, a reaction time of 3-8h, and no restriction on the reaction gas pressure because the reaction process does not involve volatile gases and special conditions. Considering the requirements of product yield and purity, energy saving and consumption reduction, etc., it is preferred to react at 180°C for 6 hours.

[0065] In the specific preparation method provided by the present invention, a bismuth source and a tungsten source are first dissolved in an organic solvent, and magnetic stirring is used in an air atmosphere for sufficient dissolution (other atmospheres such as vacuum, gas-filled protection, etc. are not excluded), and then an auxiliary agent is added to the solution, and magnetic stirring (manual stirring or oscillation mixing) is used in an air atmosphere for dissolution until the materials are fully dissolved to obtain a mixture; here, considering the economic convenience and no special requirements, electromagnetic stirring under an air atmosphere is preferred; then the mixture is placed in a high-pressure reactor for a solvent thermal reaction; the high-pressure reactor is a conventional solvent thermal reaction equipment, and those skilled in the art can select it from the prior art.

[0066] In the specific preparation method of the present invention, the product after the solvent thermal reaction is cooled, washed and dried to obtain a bismuth-based composite material.

[0067] The cooling operation of the present invention refers to natural cooling in the air by default, and does not exclude cooling processes using other forms (water cooling, oil cooling, etc.) as long as they do not affect subsequent operations. Considering the aspects of economy, environmental protection, and ease of operation, the natural cooling process in the air is preferred.

[0068] The washing in the method of the present invention adopts a multiple washing method with multiple solutions to fully remove the organic / inorganic impurities that may remain on the product after the reaction. The solution types include pure water, anhydrous ethanol, methanol, etc. At the same time, since the nanomaterial itself has a self-cleaning effect, it is not necessary to wash it when conditions permit, as long as it does not affect the subsequent product acquisition and application process. Here, in order to make the products prepared under different conditions comparative, standardized and operable, it is preferred to use pure water and anhydrous ethanol for washing 2 to 3 times each.

[0069] During the 2-3 times of washing with pure water and anhydrous ethanol in the method of the present invention, in order to avoid material loss and ensure sufficient washing, a centrifuge is used to separate the solution and the product after each washing. The speed and time of the centrifuge are not limited, as long as the product can be effectively separated.

[0070] The drying method in the method of the present invention includes natural air drying, blower drying, drying in a drying oven, etc., to ensure that the structural morphology of the product is not destroyed during the drying process and the product loss is minimized. Considering the economic, environmental and efficiency aspects, it is preferred to dry in a drying oven at 80°C for 9 hours.

[0071] By utilizing the method provided by the present invention, a bismuth-based composite material can be prepared in one step in a stable and efficient manner. The preparation process is simple, easy and environmentally friendly. The obtained product has controllable morphology, fine structure and excellent performance. The raw materials are widely available and easy to obtain. In the actual operation process, the metal ions (cations) and acid ions (anions) in the main raw materials of a reactant can respectively generate constituent elements in one or more composite products, which has the effect of reducing the length of the reaction process and reducing the carbon footprint.

[0072] The present invention finds that the synthesized bismuth-based composite material can be used as an adsorbent or catalyst to remove organic pollutants with excellent effect; specifically, the bismuth-based composite material removes organic pollutants in water by adsorbing organic pollutants in water or photocatalytically degrading organic pollutants in water; wherein, the photocatalysis adopts full-spectrum catalysis.

[0073] As a further preferred application target of the above application, the organic pollutants that can be removed by the present invention include one or more of rhodamine B, methylene blue, bisphenol A (BPA), trimethoprim (TMP), and tetracycline (TC); the selection can be made according to the degradation requirements and research problems. Here, for the convenience of observation and comparative analysis, the dye organic pollutant methylene blue is preferred. In addition, the light source in the photocatalytic application of the bismuth-based composite material of the present invention is selected from at least one or more of natural sunlight, simulated sunlight, xenon lamp, high-pressure mercury lamp, and LED monochromatic light, whichever can meet the photocatalytic degradation process.

[0074] The bismuth-based composite material prepared by the present invention can be applied to photocatalytic adsorption / degradation of organic pollutants in water in real life, and its outstanding advantage is that it can function within the full spectrum irradiation range. The actual application effect shows that the bismuth-based composite material prepared by the method provided by the present invention has excellent application performance and significant functional effect. The present invention also provides the necessary theoretical basis, process details and technical support for the preparation and application of bismuth-containing and other similar functional semiconductor materials and their composite materials.

[0075] The present invention also provides a specific method for removing organic pollutants using a bismuth-based composite material:

[0076] (1) The bismuth-based composite material is evenly dispersed in a solution containing organic pollutants and stirred for a certain period of time under light-proof conditions to achieve the effect of adsorbing and removing pollutants in the water body;

[0077] (2) The bismuth-based composite material is evenly dispersed in a solution containing organic pollutants and stirred for a certain period of time under light conditions to achieve photocatalytic degradation of pollutants in the water.

[0078] In the specific application method of the present invention, there is no clear restriction on the quality of the photocatalyst, the concentration of organic pollutants and the stirring time used, and they can be appropriately selected according to the adsorption / photocatalytic research process or actual application requirements.

[0079] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0080] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional products that can be purchased through regular channels; the raw materials and reagents used are all commercially available.

[0081] Example 1

[0082] 0.71 g WCl6 and 1.51 g BiCl3 were mixed in 60 mL acetone solution, and magnetically stirred for 1 h under air atmosphere to fully dissolve the materials to form solution A; 0.22 g CTAB was mixed in solution A, and magnetically stirred for 1 h under air atmosphere to fully dissolve the materials to form solution B; solution B was placed in a high-pressure reactor for solvothermal reaction at 180 °C for 6 h, then cooled to room temperature, washed with deionized water and anhydrous ethanol for 2 to 3 times, centrifuged, and finally placed in a drying oven and dried at 80 °C for 9 h to obtain a bismuth-based composite material BW1, the morphology of which is shown in the scanning electron microscope image as follows Figure 1 shown.

[0083] Depend on Figure 1 It can be seen that the method of the present invention is used to prepare a micro-nano aggregate composite product with good morphology, wherein the BiOCl nanosheets have a sheet diameter (length and width) of 1.5-3 µm and a thickness of 50-200 nm, and are interlaced with each other to form a three-dimensional flower-like structure; WO3 nanoparticles are uniformly dispersed on the surface or around the BiOCl nanosheets and adhere to the surface of the flower-like structure.

[0084] Figure 2 is the XRD diagram of the product obtained in Example 1, wherein BiOCl corresponds to the tetragonal-BiOCl phase, WO3 corresponds to the triclinic-WO3 phase, and the product prepared by the present invention has good crystallinity and does not contain other impurities; Figure 2 It can be seen that the bismuth-based composite material has corresponding diffraction peaks at the following diffraction positions:

[0085] PDF#06-0249: 11.98-40 (2θ-I), 25.86-100 (2θ-I), 32.50-75 (2θ-I), 3345-95 ( 2θ-I), 40.89-30 (2θ-I), 46.64-35 (2θ-I), 49.70-25 (2θ-I), 54.09-25 (2θ-I);

[0086] PDF#32-1395: 23.14-85 (2θ-I), 23.64-100 (2θ-I), 24.37-100 (2θ-I), 26.62-13 (2θ-I), 28.93-20 (2θ-I), 33.58-35 (2θ-I), 34.10-35 (2θ-I), 41.87-30 (2θ-I).

[0087] Example 2

[0088] 1.42 g WCl6 and 3.02 g BiCl3 were mixed in 60 mL acetone solution, and magnetically stirred for 1 h under air atmosphere to fully dissolve the materials to form solution A; 0.22 g ATMP was mixed in solution A, and magnetically stirred for 1 h under air atmosphere to fully dissolve the materials to form solution B; solution B was placed in a high-pressure reactor for solvent thermal reaction at 180 ° C for 6 h, then cooled to room temperature, washed with deionized water and anhydrous ethanol for 2 to 3 times, centrifuged, and finally placed in a drying oven and dried at 80 ° C for 9 h to obtain a bismuth-based composite material BW2, such as Figure 3 shown.

[0089] Depend on Figure 3 It can be seen that a product of a mixture of micron sheets and nanoparticles is prepared by the method of the present invention, wherein the BiOCl nanosheets are 2-20 µm in length and width and 200-400 nm in thickness. The nanosheets vary in size, including complete large sheet structures and broken small sheet structures. The nanosheets are interspersed and aggregated together in a stacked manner and present a flower-like structure. The nanoparticles are randomly dispersed and adhered to the surface or periphery of the nanosheets.

[0090] Comparative Example 1

[0091] Bismuth-based composite photocatalyst: BiOCl / Bi4O5Br2 was prepared by hydrothermal-precipitation reaction method.

[0092] Preparation of pure BiOCl: First, add 2mM NaCl to 50mL deionized water and stir until completely dissolved. Then add 2mM Bi(NO3)3·5H2O to the solution, mix and stir for 30min, transfer to a 100mL autoclave with a polytetrafluoroethylene liner, and finally transfer the autoclave to an oven and keep it at 160°C for 6h. After cooling to room temperature, filter the mixed liquid to obtain a white precipitate. After washing the obtained precipitate with distilled water and ethanol several times, put it in a drying oven at 60°C for 12h, and collect the dried precipitate to obtain BiOCl.

[0093] Preparation of BiOCl / Bi4O5Br2: Weigh 500 mg of the prepared BiOCl and add it to 30 mL of deionized water, mix and stir evenly, then add 25 mM NaBH4, react for 30 min, and finally filter the mixed solution to obtain a precipitate, repeat the above washing and drying operations to obtain black Bi / BiOCl. Weigh 200 mg of the prepared Bi / BiOCl and 2 g of KBr and add them to 50 mL of deionized water, mix and stir evenly, then add 5 mL of 30% H2O2 solution, react for 10 h under magnetic stirring, and finally filter the mixed liquid to obtain a precipitate, wash the obtained precipitate with distilled water and ethanol several times, put it in a drying oven at 60 ° C for 12 h, and collect the dried precipitate to obtain BiOCl / Bi4O5Br2.

[0094] It can be seen from the preparation method used in Comparative Example 1 that the bismuth-based composite photocatalyst prepared by the hydrothermal-precipitation reaction method is more complicated and cumbersome than the method used in the present invention. After the hydrothermal reaction, it is necessary to use a strong oxidant or equivalent to perform dissolution, precipitation, filtration, washing and other steps, and only a single product can be obtained at one time. Subsequent steps are still required to obtain composite bismuth materials. In addition, the adsorption effect of the prepared product on the same organic pollutants is not ideal, which is far lower than the product prepared by the present invention. Detailed data are shown in Application Examples 1 and 3.

[0095] Comparative Example 2

[0096] Preparation of bismuth-tungsten composite materials with core-shell structure: Bi / Bi2O3 / WO3.

[0097] 0.0125 mmol Na2WO4·2H2O was weighed and dissolved in 90 mL pure water, and stirred thoroughly to form solution A; 0.1 mol NaCl was weighed and dissolved in 20 mL pure water, and stirred thoroughly to form solution B; solution A was added dropwise with solution B under continuous magnetic stirring, and the mixed solution was adjusted to pH=2 with 2.5 M HCl (aq), then loaded into an autoclave, hydrothermally reacted at 180 °C for 9 h, cooled to room temperature, washed with deionized water and ethanol, centrifuged (speed 3000 r / min) for several times, and dried at 60 °C for 12 h to obtain a hydrothermal sample WO3.

[0098] 0.003 mol Bi(NO3)3·5H2O was weighed and dissolved in 60 mL ethylene glycol. After stirring at room temperature for 30 min, 0.12 g EDTA was added thereto. After further stirring at room temperature for 60 min, 0.7 g WO3 prepared by the hydrothermal method was added. After stirring evenly, the mixture was put into an autoclave and reacted at 180 °C for 9 h. The mixture was cooled to room temperature, washed with deionized water and ethanol, centrifuged (speed 3000 r / min) for several times, and dried at 60 °C for 12 h to obtain a composite sample Bi / Bi2O3 / WO3.

[0099] Although the preparation method adopted in Comparative Example 2 also prepared a tungsten-bismuth composite photocatalyst material, the preparation process was longer and more complicated than the method adopted in the present invention, and the photocatalytic degradation efficiency and effect of the prepared product on the same organic pollutants were lower than those of the product prepared in the present invention. For detailed data, see Application Examples 2 and 4.

[0100] Application Example 1 (Bismuth-based composite material of Example 1 adsorbs methylene blue and tetracycline)

[0101] 20 mg of the composite material (Example 1) was uniformly dispersed in 100 mL of 10 mg / L methylene blue (MB) / tetracycline (TC) solution, and magnetically stirred for 60 min under light-proof conditions. The supernatant was sampled at a fixed time, and the content of organic pollutants in the supernatant was detected after centrifugation, and the product adsorption efficiency corresponding to the time was calculated. The final adsorption effect is shown in Figure 4 As shown, it can be seen that the bismuth-based composite material prepared in Example 1 has a good adsorption effect on organic pollutants. At 30 min, the adsorption rate of methylene blue reaches 56%, and the adsorption rate of tetracycline reaches 30%; at 60 min, the adsorption rate of methylene blue reaches 67%, and the adsorption rate of tetracycline reaches 39%.

[0102] Application Example 2 (Photocatalytic degradation of methylene blue by the bismuth-based composite material of Example 1)

[0103] Take 20 mg of the composite material (Example 1) and evenly disperse it in 100 mL of 10 mg / L methylene blue solution. Under the condition of simulated sunlight (xenon lamp device simulation), magnetic stirring is carried out for 180 min. The supernatant is sampled at a fixed time, and the methylene blue content in the supernatant is detected after centrifugation. The product degradation efficiency corresponding to the time is calculated. The final degradation effect is as follows Figure 5 As shown, it can be seen that the bismuth-based composite material prepared in Example 1 has a good degradation effect on methylene blue, reaching more than 95% at 180 min.

[0104] Comparative Application Example 1 (Bismuth-based materials of Comparative Example 1 adsorb organic pollutants)

[0105] 50 mg of photocatalyst (Comparative Example 1) was added to a tetracycline (TC) solution (100 mL, 40 mg / L) and treated in the dark for 30 min under magnetic stirring. During the process, a constant temperature circulating water pump was used to maintain the solution temperature at 25 °C. 5 mL of the suspension was taken out at a given time interval and filtered with a water-based nylon filter membrane to obtain a pure solution. The absorbance of the solution at 357 nm was detected and recorded using a UV-visible spectrophotometer, and the removal rate of tetracycline was calculated by the absorbance. The final degradation effect is as follows: Figure 6 As shown, it can be seen that the bismuth-based material prepared in Comparative Example 1 has limited adsorption effect on tetracycline, which is less than 10% at 30 min.

[0106] Comparative Application Example 2 (Comparative Example 2: Catalytic Degradation of Organic Pollutants by Bismuth-Based Materials)

[0107] 10 mg of the composite product (Comparative Example 2) was dispersed in 100 mL of 10 mg / L methylene blue (MB) solution and stirred for 30 min in a dark environment to reach adsorption equilibrium. Then, it was placed on a xenon lamp device (420 nm filter, 20 A current) and stirred continuously to simulate the degradation process of MB under visible light. Samples were taken at fixed time intervals, and the MB content in the solution was detected after centrifugation. The degradation efficiency of the product at a certain time was calculated. The final degradation effect is shown in Figure 2. Figure 7 As shown, it can be seen that the bismuth-based material prepared in Comparative Example 2 has a certain adsorption and degradation effect on MB, with an adsorption efficiency of about 25% at 30 min, a degradation efficiency of about 77% at 180 min, and a degradation efficiency of 95% at 210 min.

[0108] It can be seen from the above adsorption effect that the bismuth-based composite material prepared by the present invention has excellent adsorption and removal effects on organic pollutants in water bodies, and the adsorption or degradation rate of MB and TC is more than twice that of comparative example 1 and comparative example 2. The overall removal effect of Example 1 of the present invention is better than that of comparative example 1 and comparative example 2 respectively; and the solvent thermal method provided by the present invention can prepare bismuth-based composite materials in one step, and the product morphology is controllable and the performance is excellent, which solves a major problem currently existing in this field and simply and stably prepares functional bismuth-based composite materials; at the same time, the raw materials used in the method of the present invention have the characteristics of many types, wide sources, large range, and easy availability on the market. The preparation process is efficient, stable, simple, easy to operate, green and environmentally friendly, and the composite product is small in size, diverse in morphology, highly controllable, and easy to use.

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A bismuth-based composite material, characterized in that: The bismuth-based composite material is a composite material of bismuth-containing nanosheets and tungsten-containing nanoparticles, which includes aggregates of the bismuth-containing nanosheets, and the tungsten-containing nanoparticles are dispersed and adhered to the surface of the bismuth-containing nanosheets; the bismuth-containing nanosheets are interpenetrated to form the aggregates; the bismuth-containing nanosheets are BiOCl nanosheets; the tungsten-containing nanoparticles are WO3 nanoparticles; the BiOCl nanosheets have a sheet diameter of 1.5-3 μm and a thickness of 50-200 nm; The preparation method of the bismuth-based composite material comprises: S1: mixing a bismuth source, a tungsten source, an organic solvent and an auxiliary agent to obtain a mixture; The molar ratio of the bismuth source, the tungsten source, the organic solvent and the auxiliary agent is (0.01-0.03): (0.01-0.08): 13.62: (0.001-0.01); the bismuth source is bismuth chloride with a concentration of 0.01-0.8 mol / L; the tungsten source is tungsten hexachloride with a concentration of 0.01-0.3 mol / L; the auxiliary agent is trimethyl 1-hexadecyl ammonium bromide with a concentration of 0.001-0.05 mol / L; the organic solvent is acetone; S2: heating the mixture under closed conditions and performing a solvent thermal reaction at a reaction temperature of 150° C. to 180° C. for a reaction time of 3 h to 6 h to obtain a bismuth-based composite material.

2. The bismuth-based composite material according to claim 1, characterized in that: The BiOCl nanosheets belong to the tetragonal system, and the WO3 nanoparticles belong to the triclinic system.

3. The bismuth-based composite material according to claim 1, characterized in that: In step S1, a bismuth source and a tungsten source are first dissolved in an organic solvent, and the solution is dissolved by magnetic stirring in an air atmosphere, and then an auxiliary agent is added to the solution, and the solution is dissolved by magnetic stirring in an air atmosphere to obtain the mixture; in step S2, the mixture is placed in a high-pressure reactor for solvent thermal reaction.

4. The bismuth-based composite material according to claim 1, characterized in that: In step S2, the product after the solvent thermal reaction is cooled, washed and dried to obtain the bismuth-based composite material.

5. The bismuth-based composite material according to claim 4, characterized in that: The washing adopts a method of multiple washing with multiple solutions; the multiple solutions include water, anhydrous ethanol or methanol; the washing includes washing with water 2 to 3 times and washing with anhydrous ethanol 2 to 3 times.

6. The bismuth-based composite material according to claim 4, characterized in that: The drying includes one or more of natural air drying, blower drying and drying oven drying.

7. Use of the bismuth-based composite material according to any one of claims 1 to 6 in removing organic pollutants.

8. The use according to claim 7, characterized in that: The bismuth-based composite material removes organic pollutants by adsorbing organic pollutants in water or photocatalytically degrading organic pollutants in water.

9. The use according to claim 8, characterized in that: The organic pollutants include one or more of rhodamine B, methylene blue, bisphenol A, trimethoprim and tetracycline.

10. The use according to claim 8, characterized in that: The photocatalysis adopts full-spectrum catalysis; the light source of the photocatalysis is selected from at least one or more of natural sunlight, simulated sunlight, xenon lamp, high-pressure mercury lamp and LED monochromatic light.